2023
DOI: 10.3389/fcvm.2023.1116509
|View full text |Cite
|
Sign up to set email alerts
|

The role of ROS-induced pyroptosis in CVD

Abstract: Cardiovascular disease (CVD) is the number one cause of death in the world and seriously threatens human health. Pyroptosis is a new type of cell death discovered in recent years. Several studies have revealed that ROS-induced pyroptosis plays a key role in CVD. However, the signaling pathway ROS-induced pyroptosis has yet to be fully understood. This article reviews the specific mechanism of ROS-mediated pyroptosis in vascular endothelial cells, macrophages, and cardiomyocytes. Current evidence shows that ROS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 126 publications
1
9
0
Order By: Relevance
“…Cell pyrolysis is involved in the emergence and advancement of many diseases, including neurological diseases, infectious diseases, inflammatory immune diseases, cardiovascular diseases, metabolic diseases. [4][5][6][7][8][9][10] The classic pyrolysis pathway is regulated caspase-1. In contrast, the nonclassical pathway of pyrolysis is regulated by caspase-4/5/11.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell pyrolysis is involved in the emergence and advancement of many diseases, including neurological diseases, infectious diseases, inflammatory immune diseases, cardiovascular diseases, metabolic diseases. [4][5][6][7][8][9][10] The classic pyrolysis pathway is regulated caspase-1. In contrast, the nonclassical pathway of pyrolysis is regulated by caspase-4/5/11.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrocytosis has been a popular research topic recently. [4][5][6][7][8][9][10] It generally occurs at the cellular level; however, it is unclear whether pyrolysis can take the lead in the treatment along with the prevision of sick people suffering from breast carcinoma. Based on the classical pathway of cell pyroptosis, we have chosen nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3), a member of the NLRs family of molecules, and the N-terminal domain of the cell pyroptosis execution protein GSDMD as our research subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that the change in the ROS level inside cells was closely related to the pyroptosis process. 34,35 To confirm this, direct H 2 O 2 -induced pyroptosis was explored in the following experiments. H 2 O 2 (0.5 mM) was added to the cells with different treatment times (0, 30, and 60 min) to induce mitochondria-associated pyroptosis.…”
Section: ■ Experimental Sectionmentioning
confidence: 91%
“…Several cardiovascular diseases, such as hypertension, atherosclerosis, diabetic cardiomyopathy, myocardial infarction, and stroke, are exacerbated by inflammation or oxidative stress ( Bai et al, 2021 ; Tian et al, 2023 ). Studies on rat models of dexamethasone (DEX) and high-fat-diet-induced programmed hypertension ( Hsu et al, 2019 ; Lin et al, 2018 ) revealed that 50 mg/kg/day of DMF induced upregulation of Nrf2 mRNA expression, along with a decrease in asymmetric dimethylarginine (ADMA) plasma levels, and the downregulation of the renin–angiotensin system.…”
Section: Novel Potential Pharmacological Applicationsmentioning
confidence: 99%